Nutritional Interventions in Chronic Disease Management: Evidence-Based Approaches for Improved Patient Outcomes - Gafiyatullina, Rezeda; Binda, Jacek (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Chronic diseases including diabetes, cardiovascular disease and obesity have a large impact on global health and effective management strategies are required. The objective of this study is to use an econometric model with data of 30 patients during 2019-2024 on how nutritional interventions in chronic disease management affect patients' outcomes. Dietary changes, supplementation, and meal plans are analyzed as to their effectiveness in individuals; socioeconomic factors are also considered as moderators. Overall, results show that the nutritional interventions have positive effects on the health markers like blood glucose level and BMI, but their effectiveness varies depending on the socioeconomic status. Interaction effects show that socioeconomic status of higher of teens’ home increased the impact of the intervention. The results indicate that personalized nutritional program, supplementing to physical activities, and broader approaches of chronic disease management are important. The findings inform evidence-based policy recommendations for successful nutritionally related interventions at the patient population level that account for different patient needs to improve chronic disease outcomes and eliminate health disparities.